Legal transplants through theoretical lens - Nguyen, Lu Quynh Anh (Đại học Quốc gia Hà Nội, 2020)
The law of Vietnam has witnessed many broken points in the historical process, from the complete changes of the legal system to adapt to the invasion and colonial regime, to reforms in each legal regime in order to gradually integrate into the global. In the process, we repeatedly lose the inheritance from history, lose our cultural and social characteristics, but also chose to receive foreign laws with a lack of consistency and rationality. However, the evaluation of theories and compatibility of the transplantation process is still lacking in scientific works, even though many of them try to incorporate comparative elements to foreign laws and international law. Therefore, in this article, the authors present the essential aspects of legal transplant processes in terms of theory, history, and the factors that impact that process in Part 2 and Part 3.